Inventarisasi Penyakit Tanaman Hortikultura Berbasis Gejala sebagai Informasi Dasar Pengelolaan Tanaman di Kebun Percobaan Leuwikopo, Kecamatan Dramaga, Kabupaten Bogor : Symptom-Based Horticultural Plant Disease Inventory as Basic Information for Plant Management in Leuwikopo Experimental Garden, Dramaga District, Bogor Regency - Khansa Amara (Agrocentrum, 2026)
A plant disease inventory is an important early approach for detecting the presence of pathogens and obtaining an overview of the distribution of plant diseases in a location. This study aims to obtain preliminary information about the group of pathogens that cause diseases in horticultural plants in Leuwikopo Plantation, Dramaga District, Bogor Regency, based on field symptom observations. The research was conducted through a field survey using visual observation methods (based on disease symptoms) and documentation of disease symptoms in various horticultural crops. The initial identification of pathogens was carried out descriptively, with reference to the morphological characteristics of common symptoms observed in the field, and data were tabulated in Microsoft Excel. Observations show that disease symptoms are caused by a group of fungi, viruses, and bacteria. Based on the proportion of symptoms in the field, fungi were the most dominant group (46.15%), followed by viruses (38.46%), with the remaining cases suspected to be caused by bacteria and parasitic plants (Cuscuta sp.). The most common symptoms of the disease are sigatoka, yellowing, and leaf stripes. The information obtained from this study is expected to serve as initial data for understanding the presence and diversity of plant diseases in the Leuwikopo Plantation. In addition, the data can serve as an initial consideration in plant disease management planning and as a basis for further research.